An entropy-driven DNA nanomachine for microRNA detection using a personal glucose meter. Issue 10 (17th January 2023) - Wang, Qing; He, Yuqiu; He, Shizhen; Yu, Shanshan; Jiang, Yuqian; Wang, Fuan
Abstract : A reliable and portable TDR-PGM nanomachine was facilely constructed for highly sensitive detection of miRNA by integrating the entropy-driven TDR amplifier and the catalytic invertase biocatalyst. Abstract : Herein, we developed a reliable and portable biosensor (TDR-PGM nanomachine) for the sensitive detection of microRNA by integrating an efficient toehold-mediated strand displacement reaction module (TDR) and a personal glucose meter (PGM). The system provides a versatile methodology for microRNA detection in real samples and holds broad prospects in point-of-care diagnosis.